Post-dynamic Resistance Exercise Hypotension: Exploring Individual Responses and Predictors - Fecchio, Rafael Y.; Queiroz, Andreia C. C.; Ritti-Dias, Raphael; Costa, Eduardo Caldas; Forjaz, Cláudia L. M. (Frontiers in Physiology, 2021)
Background: Post-dynamic resistance exercise hypotension (PREH) has been largely demonstrated. However, little is known regarding the interindividual variation of PREH magnitude and its predictors (i.e. factors of influence). Aims: To assess the interindividual variation of PREH and its predictors related to the characteristics of the individuals and the exercise protocol. Methods: This study retrospectively analysed data from 131 subjects included in seven controlled trials about PREH (including at least one dynamic resistance exercise and one control session) conducted by two research laboratories. The interindividual variation was assessed by the standard deviation of the individual responses (SDIR), and linear regression analyses were conducted to explore the predictors. Results: PREH showed moderate interindividual variation for systolic (SBP, SDIR=4.4mmHg; 0.35 standardised units) and diastolic blood pressures (DBP, SDIR=3.6mmHg; 0.32 standardised units). For systolic PREH, multivariate regression analysis (R2=0.069) revealed higher baseline SBP (B=−0.157, p=0.008) and higher number of sets (B=−3.910, p=0.041) as significant predictors. For diastolic PREH, multivariate regression analysis (R2=0.174) revealed higher baseline DBP (B=−0.191, p=0.001) and higher exercise volume (i.e. number of exercises *sets per exercise *repetitions per sets >150; B=−4.212, p=0.001) as significant predictors. Conclusion: PREH has a considerable interindividual variation. Greater PREH magnitude is observed in individuals with higher baseline blood pressure and after exercise protocols that comprehend higher number of sets and exercise volume.